2000
DOI: 10.1001/archinte.160.15.2305
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Controlled Trial of Auricular Acupuncture for Cocaine Dependence

Abstract: Findings from the current study suggest that acupuncture shows promise for the treatment of cocaine dependence. Further investigation of this treatment modality appears to be warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
93
2
3

Year Published

2001
2001
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 155 publications
(99 citation statements)
references
References 38 publications
1
93
2
3
Order By: Relevance
“…Among subjects returning to the clinic three or more times, the self-reported overall use of drugs declined during the study period, as did severity of withdrawal symptoms. Similar to other studies, 2,[8][9][10][11] we experienced a high rate of attrition among study subjects. Previous studies of community-based interventions have reported drop-out rates ranging from 34 2 to 75%.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Among subjects returning to the clinic three or more times, the self-reported overall use of drugs declined during the study period, as did severity of withdrawal symptoms. Similar to other studies, 2,[8][9][10][11] we experienced a high rate of attrition among study subjects. Previous studies of community-based interventions have reported drop-out rates ranging from 34 2 to 75%.…”
Section: Discussionsupporting
confidence: 83%
“…2 Retention in treatment was significantly associated with reduction in cocainespecific urine metabolites. In a recent trial of acupuncture for cocaine dependence, Avants et al 10 randomized subjects attending a community-based methadone maintenance program in New Haven, Connecticut, to auricular acupuncture, sham acupuncture, or a no-needle relaxation control. Subjects receiving the National Acupuncture Detoxification Association acupuncture protocol were more likely to provide cocaine negative urine samples than either the needle insertion or relaxation controls at 8 weeks.…”
Section: Introductionmentioning
confidence: 99%
“…This includes: the relevance of acupuncture for treatment of opiate based addictions (e.g. Brumbrough, 1993;Riet et al, 1990;Avants et al, 2000) and the use of Transcendental Meditation practices as successful means of treating addictions (see O'Connell and Alexander, 1994;; and cross-cultural reviews of ethnomedical approaches to addiction treatment (Jilek, 1994;Heggenhougen, 1997;Singer and Borrego, 1984).…”
Section: Introduction: Culture Consciousness and Addictionmentioning
confidence: 99%
“…In several cases, large, definitive studies that hoped to replicate promising results of initial small studies in alcohol and cocaine dependence were negative, but used auricular needling in the control group. [25][26][27][28] Researchers have used two approaches to defining a suitable sham procedure: either conjecture or empiricism. In the first, they have simply assumed that any 'incorrect' point is inactive, by what Margolin memorably termed a 'fiat'.…”
Section: Discussionmentioning
confidence: 99%